A Review of Newly Diagnosed Glioblastoma - Oronsky, Bryan; Reid, Tony R.; Oronsky, Arnold; Sandhu, Navjot; Knox, Susan J. (Frontiers in Oncology, 2021)
Glioblastoma (GBM) is an aggressive and inevitably recurrent primary intra-axial brain tumor with a dismal prognosis. The current mainstay of treatment involves maximally safe surgical resection followed by radiotherapy over a 6-week period with concomitant temozolomide chemotherapy followed by temozolomide maintenance.  This review provides a summary of the epidemiological, clinical, histologic and genetic characteristics of newly diagnosed disease as well as the current standard of care and potential future therapeutic prospects.